PONDOK PESANTREN MODERN DARUL MADINAH WONOSARI KABUPATEN BOALEMO DENGAN PENDEKATAN ARSITEKTUR TROPIS - Hendriyo Mokodompit; Nurnaningsih Nico Abdul; Elvie Fatmah Mokodongan (JAMBURA Journal of Architecture, 2023)
ABSTRACTIslamic boarding schools are religious institutions that provide education, teaching, and promote the development and dissemination of Islam. An Islamic boarding school is basically a traditional Islamic education hostel where students live and study together under the guidance of one or more teachers, known as a Kyai. The goals to be achieved at Islamic boarding schools are as follows: 1. To develop Islamic boarding school designs that cater to the needs of the space users. 2. To realize the design of Islamic boarding schools using a Tropical Architecture approach. These goals aim to review the specific aspects of the Islamic boarding schools through an architectural study, which will be presented in the form of a physical design, including: 1. Selection of an appropriate site location. 2. Determination of space requirements, room sizes, and the concept of inter-room relationships based on the users' activities at Islamic boarding schools. 3. Incorporation of the Tropical Architecture approach into the physical appearance of the building. 4. Structuring circulation and environment in an ideal building. This integration is marked by the system, curriculum, and general sciences, which are integral to Islamic boarding school teaching. In other words, modern Islamic boarding schools are educational and updated in certain aspects to suit the school system. Modern Islamic boarding schools not only organize sorongan religious lessons but also formal education activities, both the general categories (kindergarten, elementary, middle school, high school and vocational school) and Islamic religious categories (RA, MI, MTs, MA, MAK). It can be said that modern Islamic boarding schools adhere to an education system adopted from the modern education system. Additionally, the material studied is a combination of religious and general knowledge. ABSTRAK Pondok pesantren adalah lembaga keagamaan, yang memberikan pendidikan dan pengajaran serta mengembangkan dan menyebarkan agama Islam. Sebuah pondok pesantren pada dasarnya adalah sebuah asrama pendidikan Islam tradisional dimana  siswanya tinggal bersama dan belajar di bawah bimbingan seorang atau lebih dari seorang guru yang dikenal dengan sebutan seorang Kyai. Tujuan yang ingin dicapai pada Pondok Pesantren yaitu : 1. Untuk meghasilkan desain Pondok Pesantren sesuai dengan kebutuhan ruang pengguna. 2. Untuk mewujudkan desain Pondok Pesantren  dengan pendekatan Arsitektur Tropis. Sasaran yang dicapai yaitu meninjau hal-hal yang spesifik dari Pondok Pesantren dalam kajian arsitektur yang akan dituangkan dalam bentuk rancangan fisik: 1. Lokasi tapak yang memadai. 2. Kebutuhan ruang, besaran ruang, dan konsep hubungan antar ruang berdasarkan aktivitas pengguna di Pondok  Pesantren. 3. Penampilan fisik bangunan dengan  pendekatan Arsitektur Tropis. 4. Penataan sirkulasi dan lingkungan pada bangunan  yang ideal. Perpaduan ini ditandai dengan sistem, kurikulum serta ilmu- ilmu umum yang menjadi bagian integral pengajaran pesantren. Dengan kata lain, pesantren modern merupakan pendidikan pesantren yang diperbarui pada segi-segi tertentu untuk disesuaikan dengan sistem sekolah. Pesantren modern tidak hanya menyelenggarakan pengajian sorongan namun juga  menyelenggarakan kegiatan pendidikan formal, baik itu jalur umum (TK, SD, SMP, SMA dan SMK) maupun jalur berciri khas agama Islam (RA, MI, MTs, MA, MAK). Bisa dikatakan pesantren modern menganut sistem pendidikan yang diadopsi dari sistem pendidikan modern dan materi yang dipelajari merupakan kombinasi antara  ilmu agama dan umum.